Analisis Kompetensi Guru Pendidikan Islam Dalam Pengembangan Kurikulum Merdeka Menuju Local Genius 6.0 Ideas Internet Of Things (IoT) - Kurniawan, Wakib; Rohman, Miftahur; Sudrajat, Wahyu; Yana, Hawwin Huda; Nawawi, Muhammad Latif; Najah, Safiratun (Indonesia, 2024)
This research aims to analyze the competencies of Islamic Education teachers in developing the National Curriculum towards Local Genius 6.0 Ideas Internet of Things (IoT). By identifying challenges and opportunities in the implementation of IoT in the curriculum, this research explores appropriate methods to strengthen the competencies of Islamic Education teachers in Indonesia. Through a qualitative approach, data was collected through in-depth interviews and observations of Islamic Education teachers. The results show that, although there is awareness of the importance of IoT integration in the curriculum, lack of resources and lack of in-depth understanding are the main barriers. The implications of these findings highlight the need for intensive training and collaborative approaches between educational institutions and industry to strengthen teachers' competencies in the face of the IoT era. Thus, this study makes an important contribution in preparing Islamic Education teachers to be agents of change in adopting increasingly advanced technologies in the context of education.